Analisis Komunikasi Interpersonal Terhadap Kinerja Pegawai Kemendukbangga/ BKKBN Provinsi Jawa Timur - Karunia, Wilis Arum; Illah, Aina Nur; Puspita, Safriya Murni; Mohammad Khusnu Milad (PT. Intelek Cendikiawan Nusantara, 2025)
Interpersonal communication is a key factor in enhancing work effectiveness and employee performance in government organizations. This research seeks to examine the influence of interpersonal communication on employee performance at BKKBN East Java Province. Utilizing a qualitative approach, data collection methods include observation, interviews, and documentation. The results reveal that effective interpersonal communication enhances coordination, increase productivity, and create a harmonious work environment. However, several barriers hinder communication effectiveness, such as a lack of openness, differences in communication styles, rigid organizational culture, and limitations in communication technology. To address these challenges, several strategies are recommended, including enhancing communication training, promoting an open communication culture, optimizing the use of technology, and fostering more responsive leadership. With the right strategies, interpersonal communication can serve as a critical factor in improving employee performance and achieving organizational goals.